4X6 POSTER STRATEGY TOWARDS STUDENTS’ CREATIVITY AND THEIR MASTERY IN WRITING AT FBMB UNDIKMA - Firman, Edi; Hasby, M. Asrul (Jurnal Ilmiah Mandala Education (JIME), 2021)
This research was aimed 1) To find the differences between students having high creativity and students having low creativity, 2) To identify the interaction between students’ creativity and 4x6 poster strategy in their writing mastery. The research was quasi experimental. In this research, represented factorial 2X2 Analysis of Variant (ANOVA) design. Next to that, this research deal with the third semester of English department program with the total number was 80 students in which it was assumed that they have not creative in writing. Next to that, the data collected by using verbal creativity test and questionnaire. The techniques of data analysis was used descriptive analysis and inferential analysis. In analyzing data of the research the researcher used t–test formula. Based on the analysis, it was gotten that t-test score was 2.58 with the degree of freedom (df) = 78 and t-table was 2.00 at the significant level =0.05 It means that the value of t-test was bigger than t-table. Alternative hypothesis is accepted (Ha) and Null hypothesis (Ho) is rejected. In conclusion, There is a significant effect of 4x6 poster strategies towards students' creativity  at FBMB UNDIKMA (10 pt).